2021
DOI: 10.1111/jcmm.16523
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic analysis and validation of microRNA‐508‐3p as a protective predictor by targeting NR4A3/MEK axis in pulmonary arterial hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a cure-resist and chronic disease with enigmatic molecular mechanisms. 1 The aetiopathogenesis of PAH chiefly characterized by proliferation, migration, anti-apoptosis or phenotype switches of pulmonary artery smooth muscle cell (PASMC), and leading to an abnormal elevation in pulmonary arterial pressure. [2][3][4] Current treatment strategies for this disorder are palliative and do not significantly improve longterm survival. [5][6][7] Therefore, new therapies' plan is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…51 As reported, miR-508-3p is implicated in the protective mechanism of pulmonary hypertension. 24 In this study, we proved that miR-508-3p boosted HTR-8/SVneo cell progression with antioxidant defense and angiogenesis.…”
Section: Discussionmentioning
confidence: 59%
“…51 As reported, miR-508-3p is implicated in the protective mechanism of pulmonary hypertension. 24 In this study, we proved that miR-508-3p boosted HTR-8/SVneo cell progression with antioxidant defense and angiogenesis.…”
Section: Discussionmentioning
confidence: 59%
“…BMI1 [245], CCL5 [246], GREM1 [247], ANGPTL3 [248], ARG2 [249], MSRA (methionine sulfoxidereductase A) [250], SNCA (synuclein alpha) [251], NOX4 [252], PFKFB2 [253], PDZK1 [254], SUCNR1 [255], LYVE1 [256], AZGP1 [257], ERBB4 [258] and PLAT (plasminogen activator, tissue type) [259] might serve as molecular markers for kidney fibrosis. BMI1 [260], IGF2 [261], IRF7 [262], CCL5 [263], ACTN3 [264], E2F1 [265], PF4 [266], TEAD4 [267], TBX4 [268], GREM1 [269], CYP11B2 [270], WNT3A [124], COMP (cartilage oligomeric matrix protein) [271], FLI1 [272], RAP1B [273], ANGPTL3 [274], CYP3A5 [275], HSD11B2 [276], HMGCS2 [277], AGXT2 [278], SLC22A12 [279], FGF1 [280], CRY1 [281], PPARGC1A [282], SLC19A3 [283], CYP2C8 [284], ACOX2 [285], SLC2A9 [286], MSRA (methionine sulfoxidereductase A) [287], VNN1 [288], EPHX2 [289], CROT (carnitine O-octanoyltransferase) [290], SCNN1B [291], NR4A3 [292], HSD17B7 [293], SLC22A2 [294], AQP2 [295], SLC2A2 [296], EGF (epidermal growth factor) [297], ANGPT1 [298], SLC26A4 [299], KL (klotho) [300], SCNN1G [301], PDZK1 [302], PTPRD (protein tyrosine phosphatase receptor type D) [303], ACE2 [304], FOLH1 [305], SUCNR1 [306], GLCE (glucuronic acid epimerase) [307], AQP3 [308], DPP4 [309], REN (renin) [310], TRPM6 [311], ABCB1 [312], MTTP (microsomal triglyceride transfer protein) [313], CALCRL (calcitonin receptor like receptor) [314], ENPEP (glutamylaminopept...…”
Section: Discussionmentioning
confidence: 99%
“…The expression of miR‐508‐3p was decreased in gastric cancer cells, while miR‐508‐3p silencing activated NF‐κB signaling 34 . Down‐regulation of miR‐508‐3p has been reported to promote the proliferation and migration of pulmonary artery smooth muscle cells by inducing NR4A3 to activate the MAPK/ERK kinase signaling pathway, 35 which is closely related to TNF‐α expression 36 . Yan et al confirmed that miR‐508‐3p could bind to ZEB1 in colorectal cancer cells, 37 and ZEB1 knockdown reduces the expression of IL17 and other Th17 cell‐associated cytokines 38 .…”
Section: Discussionmentioning
confidence: 99%